Kungkurung of the Meratus Dayak Community, Piani Village, Tapin Regency (Study of Music Function) - Muhammad Najamudin; Wadiyo Wadiyo; Syahrul Syah Sinaga; Suharto Suharto (International Conference on Science, Education, and Technology, 2023)
Kungkurung music is a traditional South Kalimantan music made of bamboo and is identical to that of the mountain people. This music is very popular with the Dayak Meratus people of South Kalimantan. This musical instrument is found in rural areas or mountains that are overgrown with bamboo. The problem that will be raised in this study is how the history of kungkurung in the Dayak Meratus community in Piani District, Tapin Regency tho the function of kungkurung music in the Meratus Dayak community in Piani District, Tapin Regency. This study uses a qualitative method with an ethnographic approach which will be carried out in Piani District, Tapin Regency. Data collection techniques through observation, and documentation interviews. While the data analysis techniques include data collection, data reduction, and triangulation. The results of the research on kungkurung music have a history of ritual expulsion of supernatural beings that often disturb the community. The supernatural creature named Dundun ghost. Dundun's ghost often kidnaps small children in the Pipitak Jaya area. These little children always disappear when their parents are away. The function of music as an emotional expression, the function of music as an aesthetic appreciation, the function of music as entertainment, the function of music as a means of communication, the function of music as a symbol, the function of music is related to social norms, the function of music as a means of communication. Music Approval of Social Institutions and Religious Ceremonies, Functions of Music as Contribution to Sustainable Culture and Stability, Functions of Music as Contribution to Social Integration